[Translated article] Pruritus in Dermatology: Part 2-Diseases and Their Treatment - F.J. Navarro-Triviño (Elsevier, 2023)
Pruritus is the main symptom of many dermatologic and systemic diseases. Atopic dermatitis, psoriasis, contact dermatitis, urticaria, lichen simplex chronicus, mycosis fungoides, scars, autoimmune diseases, kidney or liver diseases among others are all associated with itch that may require different approaches to management. Although antihistamines seem to be the first line of therapy, in reality their role is limited to urticaria and drug-induced reactions. In fact, the pathophysiologic mechanisms of each of the conditions covered in this review will differ. Recent years have seen the emergence of new drugs whose efficacy and safety profiles are very attractive for the management of pruritus in clinical practice. Clearly, we are at a critical moment in dermatology, in which we have the chance to be more ambitious in our goals when treating patients with pruritus. Resumen: El prurito es el síntoma principal en múltiples enfermedades dermatológicas y sistémicas. La dermatitis atópica, la psoriasis, la dermatitis de contacto, la urticaria, el liquen simple crónico, la micosis fungoides, las cicatrices, las enfermedades autoinmunes, la enfermedad renal o hepática crónica, entre otras, asocian prurito que puede requerir un manejo terapéutico distinto. Aunque los antihistamínicos parecen ser la primera línea de tratamiento, en realidad su papel queda limitado a la urticaria y reacciones por fármacos, ya que los mecanismos fisiopatológicos de cada una de las entidades tratadas a lo largo de este manuscrito serán distintas. En estos últimos años han aparecido nuevas moléculas para el tratamiento del prurito, con perfiles de eficacia y seguridad muy atractivos para su uso en práctica clínica. Sin duda, es un momento crucial para el desarrollo de la dermatología en el campo del prurito, y una oportunidad para ser más exigentes con los objetivos a alcanzar en estos pacientes.